HERITAGE ASSET : PERLAKUAN AKUNTANSI ATAS BENTENG JUM PANDANG - Nur Isna (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2021)
This study aims to uncover problems related to the accounting treatment of heritage assets in terms of their recognition, valuation and disclosure in financial statements. This research is a research that uses an interpretive paradigm with qualitative methods and a phenomenological approach. Data collection is done by interview, observation, and documentation. Data analysis is done by analyzing and drawing conclusions. The results of the study showed that the historical assets of the Jum Pandang fort had met the requirements to be recognized like other fixed assets. However, in terms of assessing historical assets, Fort Jum Pandang (Fort Rotterdam) has experienced problems due to several things, namely there is no policy that regulates the valuation of historic assets and requires special personnel who understand heritage assets to assess these heritage assets. In terms of disclosure, Benteng Jum Pandang is presented and disclosed in the State Property Brief Note (CaRBMN).